The effects of intensity on VO2 kinetics during incremental free swimming - de Jesus, K.; Sousa, A.; de Jesus, K.; Ribeiro, J.; Machado, L.; Rodriguez, F.; Keskinen, K.; Vilas-Boas, J. P.; Fernandes, R. J. (Applied Physiology, Nutrition, and Metabolism, 2015)
Swimming and training are carried out with wide variability in distances and intensities. However, oxygen uptake kinetics for the intensities seen in swimming has not been reported. The purpose of this study was to assess and compare the oxygen uptake kinetics throughout low-moderate to severe intensities during incremental swimming exercise. We hypothesized that the oxygen uptake kinetic parameters would be affected by swimming intensity. Twenty male trained swimmers completed an incremental protocol of seven 200-m crawl swims to exhaustion (0.05 m/s increments and 30-s intervals). Oxygen uptake was continuously measured by a portable gas analyzer connected to a respiratory snorkel and valve system. Oxygen uptake kinetics was assessed using a double exponential regression model that yielded both fast and slow components of the response of oxygen uptake to exercise. From low-moderate to severe swimming intensities changes occurred for the first and second oxygen uptake amplitudes (P = 0.04), time constants (P = 0.01), and time delays (P = 0.02). At the heavy and severe intensities, a notable oxygen uptake slow component (>255 mL/min) occurred in all swimmers. Oxygen uptake kinetics whilst swimming at different intensities offers relevant information regarding cardiorespiratory and metabolic stress that might be useful for appropriate performance diagnosis and training prescription.